Nationwide cervical precancer screening in Ghana: concurrent HPV DNA testing and visual inspection under an expanded hub-and-spoke model - Kofi Effah; John Allotey; Ethel Tekpor; Comfort Mawusi Wormenor; Joseph Emmanuel Amuah; Ernest Antwi-Boasiako; Erasmus Nikoi Kotey; Seyram Kemawor; Isaac Gedzah; Helena Maame Ama Frempong; Stephen Danyo; Edna Sesenu; et al. (Scientific Reports)
Abstract Cervical cancer continues to disproportionately burden women in sub-Saharan Africa, and is the commonest gynecological cancer in Ghana. The Cervical Cancer Prevention and Training Centre (CCPTC), Battor, Ghana spearheaded the Ghana arm of the mPharma 10,000 Women Initiative (mTTWI) between September 2021 and October 2022. The aim of this study was to examine the outcomes of nationwide concurrent screening using high-risk human papillomavirus (hr-HPV) DNA testing and visual inspection methods, as well as factors associated with the screening outcomes. We conducted a descriptive retrospective cross-sectional study to estimate the prevalence of hr-HPV infection (nationally and regionally) and cervical lesions among women screened by graduates of our training center in their own settings (spokes) with remote supervision and mentoring by CCPTC trainers (hub). We modeled factors associated with hr-HPV infection using nominal logistic regression. Among 5217 women screened (mean age, 40.1 years), the overall prevalence of hr-HPV infection and cervical lesions were 29.1% (95% confidence interval [CI] 27.9–30.3) and 3.7% (95% CI 3.2–4.2), respectively. The prevalence distribution varied widely among regions, with the highest recorded in the Oti Region (32.8%) and the lowest recorded in the Upper West (20.7%) and North-East (20.7%) regions. The most frequently detected HPV genotype was other hr-HPV type(s) only (non-HPV16, non-HPV18) (23.5%; 95% CI 22.3–24.7), followed by HPV16 only (1.5%; 95% CI 1.2–1.8), and mixed infection with HPV18 + other hr-HPV type(s) (1.2%; 95% CI 0.9–1.5). Factors found to be significantly associated with hr-HPV infection among women screened included age < 35 years, having a relationship status apart from married/cohabitation, nulliparity, and HIV positivity. Drawing from our implementation of this model within the mTTWI, we posit that while Ghana prepares for organized screening, coordinating opportunistic screening could enable a phased expansion of cervical precancer screening with the help of international and local partners. This approach, combined with concurrent testing (hr-HPV DNA testing and visual inspection), holds promise for mitigating loss to follow-up among women requiring additional evaluation and lesion management.